The Impact of COVID-19 on the Cypriot Stock Market Dynamics - Christodoulou-Volos, Christos; Tserkezos, Dikaios (International Journal of Economics and Financial Issues, 2024)
This paper examines the effects of coronavirus disease 2019 (COVID-19) pandemic outbreak on the Cypriot Stock Exchange (CSE), which has encountered substantial turmoil. For this purpose, daily stock market returns were used over the period of September 3, 2019 - July 10, 2020, for the Cypriot economy. The study applied Granger causality models to explore whether the CSE is impacted by the crisis generated by novel coronavirus. Hsiao’s approach to Granger causality was employed to investigate the causalities among COVID-19 and stock market returns, as well as between pandemic measures and several commodities. The analyses uncover intricate dynamics and contributing factors, shedding light on the observed volatility. The findings demonstrate significant volatility throughout the pandemic, with notable shifts in market conditions. Nevertheless, the stock market showcased resilience and recovery during the initial shutdown period. These insights contribute to understanding the pandemic’s impact on the CSE, offering crucial guidance for investors, policymakers, and market participants.